Makna Simbolik Kehidupan Penyair dalam Puisi “Capungku” Karya Zawawi Imron - Ulum Janah; Anna Anganita Theresia Latumeten (Prologue: Journal on Language and Literature, 2023)
Poetry is a form of literature that is not only in the form of beautiful words, but also has a deeper meaning for the poet himself (the poet). Poetry becomes an expression of the contents of the heart that describes the poet's life and experiences. Through a qualitative method with a semiotic approach, this study tries to reveal the poet's life by determining the syntagmatic and paradigmatic of the Poetry "Capungku" by Zawawi Imron. The results of this study can be seen from the side of happiness that goes hand in hand with jealousy in the poet's social life. One side of the poet has a desire to be happy, but sometimes this contrasts with the other side which has jealousy and the social environment which often has an influence on the poet himself. This is a problem in human life whoever it is. Both are mirrors of a human life that will always be contradictory.